Retinal Laser Photocoagulation - Naning Suleman (Jambura Medical and Health Science Journal, 2022)
Background: Panretinal photocoagulation (PRP) is the standard gold therapy to prevent vision loss in severe non-proliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR).Contents: Photocoagulation is a therapeutic technique using a solid light source to coagulate tissue. This light energy is absorbed by the retinal tissue and converted into thermal energy. This energy then causes the abnormal blood vessels in the retina to shrink and disappear. It takes approximately 6-8 weeks for complete shrinkage of blood vessels.Conclusion: Laser retinal photocoagulation is the standard therapy in diabetic retinopathy patients. By causing thermal lesions of the pathological retinal vessels, the expected outcome can be achieved in 2-3 months of therapy.